2010
DOI: 10.1039/b925710a
|View full text |Cite
|
Sign up to set email alerts
|

Complementary halogen and hydrogen bonding: sulfur⋯iodine interactions and thioamide ribbons

Abstract: Complementary halogen bonding and hydrogen bonding coexist in co-crystals of organoiodines with molecules containing the thioamide functionality. Thiourea.organoiodine co-crystals are shown to exhibit a remarkably reliable synthon with complementary N-H...S ribbons and S...I interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 34 publications
7
71
1
Order By: Relevance
“…This ability of the thione sulfur atoms to interact with more than one XB donor has been mentioned in a few examples with organic XB donors 18,19,30 while it is essentially unknown with the thione adducts with I 2 , Br 2 , IBr or ICl (see below). This ability of the thione sulfur atoms to interact with more than one XB donor has been mentioned in a few examples with organic XB donors 18,19,30 while it is essentially unknown with the thione adducts with I 2 , Br 2 , IBr or ICl (see below).…”
Section: Scheme 2 Investigated Iodinated Dithiole-2-thiones and Thiazmentioning
confidence: 97%
See 1 more Smart Citation
“…This ability of the thione sulfur atoms to interact with more than one XB donor has been mentioned in a few examples with organic XB donors 18,19,30 while it is essentially unknown with the thione adducts with I 2 , Br 2 , IBr or ICl (see below). This ability of the thione sulfur atoms to interact with more than one XB donor has been mentioned in a few examples with organic XB donors 18,19,30 while it is essentially unknown with the thione adducts with I 2 , Br 2 , IBr or ICl (see below).…”
Section: Scheme 2 Investigated Iodinated Dithiole-2-thiones and Thiazmentioning
confidence: 97%
“…Most of the reported examples involved either sp 3 sulfur atoms in thioethers or sp 2 sulfur atoms in thiones and thioureas, interacting with I 2 , IBr or ICl. One can essentially mention (Scheme 1) the co-crystals of thiourea, ethylenethiourea, 18 2-mercapto-1methyl-imidazole 19 or primary thioamides, 20 with strongly activated halogen bond donors such as 1,2-and 1,4diiodotetrafluorobenzene. 5 In this context, it is quite surprising that this wide pool of sulfurbased XB acceptors has not been engaged extensively in XB systems with other XB donor molecules than the dihalogens and interhalogens.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be much more interesting to contrast the behavior of XB donors 2-4 with A and D to that with A and C. Especially with 2, the isolation of two stoichiometric variations, A·D·2 2 Initially, A·D·2 2 is formed as the kinetic product, with A and D assembling into motif I and 2 only serving as a monotopic halogen bond donor, not utilizing its full potential (Figure 3a). 33 The system evolves, however, resulting in the formation of A·D 2 ·2 2 with the re-emerging motif II, and the formation of chains through N−H···S hydrogen bonds supported by C−I···S and C−I···O halogen bonding with 2 again acting as a ditopic donor (Figure 3b). Next, the structure of A·D 2 ·3 2 , featuring thiourea D in the more stable cis conformation 40 still exhibits motif II, with A·D 2 moieties connected into chains through C−I···S halogen bonds with XB donor 3 (Figure 4a).…”
Section: Scheme 3 Hydrogen Bond-mediated Binding Motifs Between Crowmentioning
confidence: 99%
“…Arman et al reported that the N−H···S type hydrogen bonding between thiourea-type molecules is preserved in the structures of their C−I···S halogen bonded co-crystals. 33 Moreover, the set of cocrystals described consisted of three different thioureas and three different halogen bond donors, suggesting that the orthogonality of hydrogen and halogen bonding could be a general property of such systems. Later, Robertson et al showed the halogen bonds between diiodine as the donor and tetramethylthiourea as the acceptor to be particularly robust in solution, which was ascribed to their pronounced charge-transfer character.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between hydrogen and halogen bonding in sulfur-containing systems has potential relevance for thyroid chemistry [115,116] and as such a study of the cooperative effects between these and other non-covalent interactions in model systems may provide a better understanding of the structure and properties of related biomolecular complexes, especially those that may govern important biological activities in living systems. structures that these dimers adopt.…”
Section: Thiirane Xf/beh 2 Dimersmentioning
confidence: 99%